Optimization of preparation techniques for high-temperature resistant waterborne phenolic-epoxy resin emulsion under low carbon background - Lu, Yu; Gu, Jing; Yuan, Jinhe; Wu, Lina; Wang, Xinxin; Xu, Xiaofang; Ye, Fuqiang; He, Libin (Frontiers in Materials, 2024)
In light of escalating global climate change concerns and the pressing need to address industries with high carbon emissions and pollution, enhancing the preparation of phenol-formaldehyde epoxy resins has emerged as a critical research focus. This study seeks to fabricate waterborne phenolformaldehyde epoxy resins with superior performance by investigating pivotal factors influencing their properties and refining preparation methods. Utilizing tetrabutylammonium bromide as a phase transfer catalyst, the phenol-formaldehyde epoxy resins are synthesized via a two-step alkalization process. Subsequent etherification reactions involve modifying the phenol-formaldehyde epoxy resins using cationic modifier diethanolamine (DEA) and anionic modifier sodium p-amino benzenesulfonate, resulting in waterborne phenol-formaldehyde epoxy resins. Subsequently, in-situ synthesis is employed to produce nanoscale silica (SiO2) modified waterborne phenol-formaldehyde epoxy resins. The findings reveal that when the ratio of n1 to n2 falls within the range of 1/3.25 to 1/3, the emulsion displays a moderate particle size and maintains stable storage. Furthermore, an increase in DEA dosage leads to a particle size of less than 324nm when the ratio of n1 to n2 exceeds 1/3, indicating stability. Moreover, optimal stability and prolonged storage lifespan are achieved when the nano SiO2 content is approximately 1.5%. This study contributes by synthesizing highquality waterborne phenol-formaldehyde epoxy resin emulsions through optimized methods. The research findings offer a theoretical foundation for this domain and support the practical application of low-carbon and environmentally friendly concepts in the coatings industry.